A escolarização no Oeste do Paraná: Os grupos escolares de Medianeira (1950-1978) - de Paula, Sander Fernando (2020)
This research analyzed the constitution of the School Groups in the municipality of Medianeira between the years 1950-1978, date of the beginning of the colonization of Medianeira until the decree Nº 4,558 of January 20, 1978, of the Government of the State of Paraná. We aim to understand the historical, political and economic determinants that influenced the emergence of school groups in the municipality. We related history, memory and education as foundations for the studies of History of Education, from the survey of official and unofficial documentary sources, in order to contribute to the research and preservation of sources of History of Education in the West of Paraná. We use a qualitative approach, through bibliographic research and documentary sources, relevant in this context because it is a process of reflection on reality through methods and techniques for understanding the object, in which it will be studied within its historical context. We research literature referring to the object studied, reports and detailed analysis from official and unofficial sources. Although far from the reality of the most developed urban centers, the school groups of Medianeira, in its regional peculiarities represented the civilization process. It was the symbol of progress and patriotism, spread in the cities of the interior of the State. When it comes to research on the history of education, the sources are loaded with social memories, covering all the historicity of these institutions, primordial in educational research. We hope to contribute to new studies in the history of education.